Scientific and Philosophical Rationality in Geography: A Synthesis of Madilog, Western and Islamic Philosophy in Indonesian Environmental Ethics and Culture - Ahmad Fauzi; Ahman Sya; Wini Mustikarani (Civilization Research: Journal of Islamic Studies, 2026)
Rationality constitutes a fundamental foundation for developing geography as a scientific discipline in understanding the relationships among humans, the environment, and culture. Geography requires an epistemological framework that integrates scientific, philosophical, and ethical dimensions during increasingly complex environmental challenges. Nevertheless, studies synthesizing scientific rationality, Western philosophy, Tan Malaka’s Madilog (Materialism, Dialectics, and Logic), and Islamic philosophy within geographical studies remain limited. Therefore, this study aims to analyze the concept of rationality in geography by integrating these philosophical traditions to strengthen environmental ethics and develop a more comprehensive geographical epistemology. This research employed a qualitative method using a library research approach by examining primary and secondary literature on philosophy, philosophy of science, geography, Islamic philosophy, and Madilog. Data were analyzed using descriptive-analytical techniques through comparison, interpretation, and conceptual synthesis of relevant philosophical perspectives. The findings reveal that scientific rationality provides empirical verification and methodological rigor, Western philosophy contributes to logical and critical reasoning, Madilog strengthens dialectical and contextual analysis of socio-environmental realities, and Islamic philosophy enriches geographical thought by integrating reason, revelation, and spiritual values into environmental ethics. The synthesis of these perspectives produces a holistic epistemological framework that enhances the understanding of human–environment interactions and promotes scientific, cultural, and religious values-based ecological awareness. The novelty of this study lies in the integration of scientific rationality, Western philosophy, Madilog, and Islamic philosophy into a unified geographical epistemology that incorporates ethical and spiritual dimensions and extends beyond conventional empirical approaches. The findings also have important policy implications for strengthening environmental education, integrating environmental ethics into geography curricula, and supporting sustainable environmental governance through culturally and spiritually informed approaches.